Adaptation to climate change and integration of disaster risk management in business education: a case study in Fundação Getulio Vargas, Brazil (2016)
The aim of this paper is to discuss improvements for the Master in Sustainability Management of Fundação Getulio Vargas (Getulio Vargas Foundation - FGV), in order to incorporate the topic of disaster risk management (DRM). Considering the risks and opportunities that climate change – and more specifically extreme weather events that can lead to disasters – represent to business, it is essential that business schools help prepare managers to deal with this critical sustainability issue. Therefore, it is extremely important to include this topic in management education. Aiming to support companies to assess and address business risks and opportunities derived from climate change, the Business for Climate Platform (EPC) of the Center for Sustainability Studies (GVces) of FGV has developed a framework and a tool for business adaptation strategies for climate change and implemented them with seven large companies in Brazil. Thus, based on EPC’s experience, the paper brings a proposal for the inclusion of DRM in the MSM’s syllabi, through the lens of climate change adaptation